Enhanced dielectric, ferroelectric, and electrostrictive properties of Pb(Mg1/3Nb2/3)0.9Ti0.1O3ceramics by ZnO modification - Methee Promsawat (2018)
The effects of ZnO modification on the dielectric, ferroelectric, and electrostrictive properties of 0.9Pb(Mg1/3Nb2/3)O3-0.1PbTiO3(PMNT) ceramics are systematically studied in this work. The PMNT/xZnO (with x = 0, 0.4, 2.0, 4.0, and 11.0 mol. %) ceramics of complex perovskite structure were prepared by solid state reaction and sintering process. It is found that the maximum value of the dielectric constant decreases with increasing ZnO amount up to x = 4.0 mol. %, and then significantly increases with x = 11.0 mol. %. The temperature of maximum dielectric constant tends to increase, while the diffuseness of the dielectric peak is reduced, with increasing ZnO content. The remanent polarization and the coercive field increase with increasing ZnO concentration. The induced strain and the electrostrictive coefficient reach the maximum values of 0.10% (at E = 10 kV/cm) and 12.94 × 10-16m2/V2, respectively, with x = 2.0 mol. % ZnO. The ceramic doped with a high ZnO content (11.0 mol. %) exhibits a macroscopically polar phase with a well-developed ferroelectric hysteresis loop and butterfly-shaped bipolar piezoelectric response. This enhanced long-range polarization and the resulting properties are attributed to the effects of the partial substitution of Zn2+for Mg2+, which favors a higher degree of polar order and a lower degree of relaxor behavior. © 2013 AIP Publishing LLC.